Road Infrastructures and Projectual Logics: Spatial relations between Avenida Brasil and the metropolitan territory of Rio de Janeiro - Moraes, Pedro Barreto de (Risco - Journal of Architecture and Urbanism, 2021)
This article proposes a reading on the urban morphology of the territories connected to Avenida Brasil, in Rio de Janeiro, based on the research for a more balanced structuring of the metropolis. Firstly, some of the parameters that guided the implementation of the road and conditioned its spatial conformation are exposed, followed by a description of its metropolitan insertion. Lastly, five relational categories are proposed, articulating infrastructure and territory and pointing to final reflections raised by their understanding. The main objective of this work is the development of a vocabulary better suited to the complexity of the scenarios conformed by large road infrastructures, in order to contribute to the advancement of new urban design and planning instruments.